2000
DOI: 10.1103/physreva.61.063806
|View full text |Cite
|
Sign up to set email alerts
|

Atom localization via resonance fluorescence

Abstract: We propose a simple scheme of atom localization based on resonance fluorescence from a standing-wave field. The Rabi frequency is position dependent and therefore the spontaneously emitted photon carries the information of the atomic center-of-mass motion. This leads to atom localization even during the flight through the standing-wave field.PACS number͑s͒: 32.50.ϩd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(122 citation statements)
references
References 21 publications
1
120
1
Order By: Relevance
“…We study expression (14) for the imaginary part of the susceptibility on the probe transition in greater detail in the following discussion. It is clear that χ ′′ -i.e., the probe absorption-depends on the controllable parameters of the system like probe field detuning and amplitudes and phases of the driving fields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We study expression (14) for the imaginary part of the susceptibility on the probe transition in greater detail in the following discussion. It is clear that χ ′′ -i.e., the probe absorption-depends on the controllable parameters of the system like probe field detuning and amplitudes and phases of the driving fields.…”
Section: Resultsmentioning
confidence: 99%
“…We consider some of these proposals in detail to contrast them with the current proposal. Qamar et al [14] suggested a simple scheme for localization of an atom by using a simple twolevel system interacting with the classical standing-wave field. They showed that the frequency of the spontaneously emitted photon carries information about the position of the atom.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of interference of two waves with wavevectors k 1 and k 2 , the optical field is (10) and intensity distribution is given by (11) intensity at different spatial position changes between (|E 1 |−|E 2 |) 2 and (|E 1 |+|E 2 |) 2 . Introducing G = 2|Ω 0 | 2 T 1 T 2 , we can write (12) Then, for the drive field at the position being near to its zero the Rabi frequency is given by (13) where…”
Section: Two-level Atomsmentioning
confidence: 99%
“…Microscopy with classical fields can be enhanced by the nonlinear optical response of the medium [4]. Classical field amplitude and phase arrangements can be used to locate the position of an atom with subwavelength precision in an atomic beam [5,6,7], in a cavity [8], and then to apply localization technique to lithography [9,10,11], and to achieve subwavelength diffraction and imaging with classical light using the Doppleron-type resonances [12,13]. Beating diffraction limit was experimentally demonstarted [14] using the dark states.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The quantum coherence effects observed in light-matter interactions have also been applied to an entirely different area of atomic manipulations, namely atom optics. There exist schemes for localization of moving atoms as they pass through the standing wave field of a cavity by monitoring spontaneous emission spectrum [11][12][13][14][15][16] and by monitoring absorption of a weak probe field.…”
Section: Introductionmentioning
confidence: 99%